The Creation of Android-Based Educational Resources For Students of Physical Education And Health Enrolled In Introductory Computer Courses at Hamzanwadi University - Fathoni, Ahmad; Kuswanto, Heri; Hariadi, Hariadi; Suryansah, Suryansah (Musamus Journal of Physical Education and Sport (MJPES), 2025)
The physical education study program predominantly employs a model of learning that focuses on lectures and presentations by nearly all lecturers. This affects many students who are not enthusiastic about following basic computer lessons, which impacts the teaching and learning process that occurs in the classroom. There is currently no maximum limit regarding the existence of Android-based learning media focused on computer subjects, particularly within the physical education study programs at Hamzanwadi University, which can serve as a valuable resource. Examine students to understand how participants perceive boredom during learning activities, particularly in computer-based subjects. Objectives. The purpose of this study is to develop a decent Android-based learning media. For the application of teaching materials for students in the subject of computer basics, it is essential to understand the feasibility of using Android-based learning media as effective teaching resources for this subject. Materials and Methods. This involves the advancement of study (Research and Development). The model employed for development is the ADDIE model. The data utilized is quantitative, and the technique for data collection involves the use of a questionnaire. Analyzing data techniques in the study This is a form of quantitative analysis that focuses on describing characteristics and patterns within data. Results. The study results indicate that the Android learning media teaching materials are affirmed. The evaluation indicates that the material is deemed very worthy by experts, with a percentage of 90%. Media experts also rated it as very worthy, giving it a score of 83%. Additionally, user responses reflect a very high rating, with a percentage of 85%. Conclusions. The Decent Android learning media serves as an effective teaching material for educational purposes.